2010
DOI: 10.1093/molbev/msq335
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Rubisco Kinetics during the Evolution of C4 Photosynthesis in Flaveria (Asteraceae) Are Associated with Positive Selection on Genes Encoding the Enzyme

Abstract: Rubisco, the primary photosynthetic carboxylase, evolved 3-4 billion years ago in an anaerobic, high CO(2) atmosphere. The combined effect of low CO(2) and high O(2) levels in the modern atmosphere, and the inability of Rubisco to distinguish completely between CO(2) and O(2), leads to the occurrence of an oxygenation reaction that reduces the efficiency of photosynthesis. Among land plants, C(4) photosynthesis largely solves this problem by facilitating a high CO(2)/O(2) ratio at the site of Rubisco that rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
117
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(122 citation statements)
references
References 55 publications
5
117
0
Order By: Relevance
“…However, A281 packs against S321 and G322 at the end of the strand, which leads to loop 6, and destabilization of this interaction may have a long-range effect on the dynamics at the active site. Another frequently positively selected mutation, M309I, also identified in some previous phylogenetic studies (20,24), lies at the interface of the two C-terminal domains within a dimer and also close to the junction between N-and C-terminal domains within each subunit. This mutation has been demonstrated to act as a catalytic switch between C 3 -like and C 4 -like properties (i.e., decreasing specificity for CO 2 over O 2 and increasing the turnover) in Flaveria species and in chimeric enzymes consisting of large subunits from Flaveria and tobacco small subunits (21).…”
Section: Analysis Of Mutations Occurring During Evolution and Their Ementioning
confidence: 62%
See 2 more Smart Citations
“…However, A281 packs against S321 and G322 at the end of the strand, which leads to loop 6, and destabilization of this interaction may have a long-range effect on the dynamics at the active site. Another frequently positively selected mutation, M309I, also identified in some previous phylogenetic studies (20,24), lies at the interface of the two C-terminal domains within a dimer and also close to the junction between N-and C-terminal domains within each subunit. This mutation has been demonstrated to act as a catalytic switch between C 3 -like and C 4 -like properties (i.e., decreasing specificity for CO 2 over O 2 and increasing the turnover) in Flaveria species and in chimeric enzymes consisting of large subunits from Flaveria and tobacco small subunits (21).…”
Section: Analysis Of Mutations Occurring During Evolution and Their Ementioning
confidence: 62%
“…The high concentration of CO 2 at the site of RubisCO in C 4 plants allows a lower specificity ratio of CO 2 /O 2 and therefore an increase in turnover rate and thus efficiency (17,18). Experimental studies of RubisCOs from very closely related C 3 and C 4 species within the Flaveria, Atriplex, and Neurachne genera showed that very few changes may be necessary to modify enzymatic properties in response to the modification of the metabolic context (19,20). Indeed, in the Flaveria context, a single mutation (M309I) has been identified as key in modifying specificity and increasing turnover (21); it remains unclear as to how this observation applies to a wider range of plants and what the contributions are of other observed mutations to adaptation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In land plants, it has been established that positive selection in rbcL emerges coincident with the development of a C 4 CCM which elevates CO 2 to almost saturation at the site of Rubisco [55,56]. This relaxes pressure for Rubisco to have a high affinity for CO 2 and therefore allows an increase in V c , which results in increased photosynthetic efficiency as the plant requires less nitrogen to achieve a given CO 2 [4,6,20] and K c (dark blue bars) [6,21] with standard error bars and number of species measured (n) are shown.…”
Section: Resultsmentioning
confidence: 99%
“…This relaxes pressure for Rubisco to have a high affinity for CO 2 and therefore allows an increase in V c , which results in increased photosynthetic efficiency as the plant requires less nitrogen to achieve a given CO 2 [4,6,20] and K c (dark blue bars) [6,21] with standard error bars and number of species measured (n) are shown. [55,56]. By analogy, therefore, positive selection in Rubiscos of the Haptophyta and diatoms is likely to have occurred also in response to emergence of CCMs as both Haptophyta and diatoms are thought to possess them [57].…”
Section: Resultsmentioning
confidence: 99%